BEHAVIORAL FLEXIBILITY AS A CONDITION SUCCESS IN PROFESSIONAL ACTIONS EDUCATION MANAGER (Pedagogy of Higher and Secondary Education, 2008)
In clause the essence of behavioral flexibility, as one of the important conditions of professional actions of the manager of formation reveals. Aspects of professional competence of the manager of formation are staticized.